Desenvolvimento de um rastreador solar open loop e um banco de dados de posicionamento solar no município de Francisco Beltrão – Paraná - Toniazzo, Fernando (2021)
The work in question aimed to develop a microcontrolled solar tracker and generate data to assist in the positioning of solar collectors in the city of Francisco Beltrão, Paraná. The calculations referring to the orientation of the collectors are based on the methodology of Duffie & Beckman (2006), which determines angular coordinates of the solar positioning and the positioning of solar collector surfaces. The positioning of the solar tracker was aided by an Arduino microcontroller, which manages two stepper motors responsible for moving two axes of rotation. The structure of the solar tracker was made of metallic material to support the weight and condition the engines responsible for its dynamics. The positioning data was based on the municipality of Francisco Beltrão (26.05S, 53.04W) and the angles of azimuth and inclination of the collecting surface as a function of time (from 6 am to 6 pm) were presented. The results for the characterization of the positioning of solar collectors in Francisco Beltrão show that the average annual value of inclination at noon, approaches the degree of inclination suggested in the literature for fixed systems that is equal to the degree of local latitude for each region. As for the mathematical model, it presented satisfactory precision values with average relative differences of 0.25% for solar azimuth and 0.23% for solar altitude when compared with other authors. The solar tracker proved to be accurate when positioned in relation to the luminous bulkhead, which maintained the perpendicularity in relation to the installed plane and the circular shading was maintained throughout the solar trajectory.